Ricin and Shiga Toxins Pathogenesis, Immunity, Vaccines and Therapeutics - Mantis, Nicholas.; Mantis, Nicholas. (Current Topics in Microbiology and Immunology,, 2012)
The intent of this volume of Current Topics in Microbiology and Immunology was to bring together a collection of in-depth and cutting edge reviews that highlight our current understanding of the biology of ricin and Shiga toxin (Stx), with the long term goal of advancing the development of countermeasures against these toxic agents.  In May of 2011, Western Europe experienced a severe outbreak of Stx-producing E. coli (STEC) that culminated in more than 3200 cases and 39 deaths.  While Stx is not the only virulence factor associated with STEC, it is certainly the primary determinant associated with the onset of hemolytic uremic syndrome (HUS).  At the present time, there are no clinically approved measures to neutralize Stx in individuals suffering from STEC infection.  Nor are there any preventatives or therapeutics for ricin toxin.  Although incidents of ricin exposure are largely unheard of, federal agencies and public health officials consider it a significant threat.  It is well documented that domestic and international terrorist groups have stockpiled, and in some cases weaponized ricin with the intent of releasing it into the public sphere and causing panic, illness and/or death on a local, regional, or possibly national scale. As the title of this volume indicates, the chapters, written by leading experts in the field, are organized so as to cover all aspects of ricin and Stx, including pathogenesis, immunity, vaccines and therapeutics. This outstanding collection of reviews will serve as an important and readily accessible resource for the research community in the coming years.   .